2009
DOI: 10.1016/j.vetimm.2008.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of the C2 canine mastocytoma cell line to the effects of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a member of the TNF family, which preferentially induces apoptosis in cells that have undergone malignant transformation. In humans, non-neoplastic cells are normally protected from the effects of TRAIL by expressing decoy receptors, lacking death domains. In contrast, neoplastic cells tend to downregulate their decoy receptor expression, increasing their susceptibility to the pro-apoptotic effects of TRAIL, via the functional TRAIL receptors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…However, the infected animals were protected even at early stages of the infectious period without increased TRAIL expression because 3,4-diCQA increases the viability of infected cells, as suggested by previous ex vivo experiments [31]. It must be noted that MDCK cells do not express the TRAIL receptor [44]. 3,4-diCQA induced TRAIL mRNA at 7 dpi relative to the control group (Figure 3).…”
Section: Discussionsupporting
confidence: 51%
“…However, the infected animals were protected even at early stages of the infectious period without increased TRAIL expression because 3,4-diCQA increases the viability of infected cells, as suggested by previous ex vivo experiments [31]. It must be noted that MDCK cells do not express the TRAIL receptor [44]. 3,4-diCQA induced TRAIL mRNA at 7 dpi relative to the control group (Figure 3).…”
Section: Discussionsupporting
confidence: 51%
“…The human and dog TRAIL sequence identity is 81.3%, and the amino acid sequences of the trimeric or receptor‐binding domains of TRAIL are highly conserve . A previous study showed that rhTRAIL, the same as TRAIL‐TEC used in this study, induced apoptosis in a canine mastocytoma cell line . Of the three rhTRAIL proteins examined, izTRAIL showed the strongest ability to induce apoptosis in canine HSA cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many normal cells are resistant to apoptosis induced by TRAIL. In veterinary medicine, a study on the effect of TRAIL on canine mast cell tumour cell lines revealed a role of the activation of caspase‐3 . In addition, caspase‐8 was shown to be activated by flavopiridol (FVP) in lymphoma cell lines exhibiting TRAIL resistance, but it is not clear whether TRAIL activated caspase‐8 as well .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations